2004
DOI: 10.1203/01.pdr.0000106315.00474.6f
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Cationic Protein in Human Milk Is Associated with Development of Cow's Milk Allergy and Atopic Eczema in Breast-fed Infants

Abstract: The precise role of leukocytes and mediators in human milk is still unresolved. Eosinophils are uncommonly detected in human milk and their presence has previously been associated with maternal atopy and development of cow's milk allergy (CMA) in the breast-fed infant. The purpose of this study was to examine the levels of eosinophil cationic protein (ECP) in human milk and to compare the levels with development of allergic diseases in breast-fed infants. Altogether 94 breast-feeding mothers (58 atopic, 36 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
(38 reference statements)
1
9
0
1
Order By: Relevance
“…Moreover, Altman et al [30] have demonstrated that eosinophil granule products caused significant up‐regulation of ICAM‐1 on human nasal epithelial cells in vitro . We have previously found increased levels of eosinophil cationic protein (ECP) in the milk of mothers with food‐allergic infants [31]. These increased numbers of neutrophils found in mother's milk might hypothetically serve as storage of ECP because it is reported that ECP is actively taken up by neutrophils and stored in the granules of these cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Altman et al [30] have demonstrated that eosinophil granule products caused significant up‐regulation of ICAM‐1 on human nasal epithelial cells in vitro . We have previously found increased levels of eosinophil cationic protein (ECP) in the milk of mothers with food‐allergic infants [31]. These increased numbers of neutrophils found in mother's milk might hypothetically serve as storage of ECP because it is reported that ECP is actively taken up by neutrophils and stored in the granules of these cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…4 All available samples were assessed from 39 mothers of non-CMA infants and 35 mothers of CMA infants, verified by oral food challenges 6 performed at median 5.5 months of age (IQR, 3.1–7.7 months). Clinical characteristics are shown in Table E1.…”
Section: To the Editormentioning
confidence: 99%
“…Logistic univariate regression was then used to assess the influence of multiple immunologic factors in human milk on CMA onset, including milk immune markers, leukocytes, eosinophilic cationic protein (ECP), and the levels of β-lactoglobulin (BLG)- and casein-specific IgA, which have been previously reported in this cohort. 46 After adjusting for maternal covariates, including atopic diseases, age and duration of lactation, the levels of IL-1β (p=0.001), IL-10 (p=0.04) and BLG-specific IgA (p=0.005) were lower in the milk of mothers with a CMA infant than in those with a non-CMA infant and there was a trend for lower IL-6 (p=0.07, Table EIII). …”
Section: To the Editormentioning
confidence: 99%
“…11 Higher levels of eosinophil cationic protein in breast milk have been associated with a higher incidence of cow's milk allergy and atopic dermatitis in infant recipients. 12 It is unclear how these disparate mechanisms of immunomodulation express themselves in infant mother pairs or whether one will be able to predict, on a case by case basis, how breast milk will effect the development of allergies in a given child. Perhaps an understanding of genetic factors may allow for better predictability in the future.…”
Section: Immunologic Complexity Of Breast Milkmentioning
confidence: 99%